Climate change adaptation planning in large cities: A systematic global assessment. Issue 66 (December 2016) - Araos, Malcolm; Berrang-Ford, Lea; Ford, James D.; Austin, Stephanie E.; Biesbroek, Robbert; Lesnikowski, Alexandra
Highlights: We develop a framework for assessing climate change adaptation planning in cities. Only 73 of 401 (18%) municipalities report adaptation planning activity. Cities report diverse climate impacts and affected sectors as motivations to adapt. Differences in government structures may explain variations in reporting. Some cities profiled as extensive adaptors are located in low-income countries. Abstract: Cities globally face significant risks from climate change, and are taking an increasingly active role in formulating and implementing climate change adaptation policy. However, there are few, if any, global assessments of adaptation taking place across cities. This study develops and applies a framework to track urban climate change adaptation policy using municipal adaptation reporting. From 401 local governments globally in urban areas with >1 m people, we find that only 61 cities (15%) report any adaptation initiatives, and 73 cities (18%) report on planning towards adaptation policy. We classified cities based on their adaptation reporting as extensive adaptors, moderate adaptors, early stage adaptors, and non-reporting . With few exceptions, extensive adaptors are large cities located in high-income countries in North America, Europe, and Oceania, and are adapting to a variety of expected impacts. Moderate adaptors usually address general disaster risk reduction rather than specific impacts, and are located in a mix of developed and developing countries. Early stage adaptors exhibit evidence of planning for adaptation, but do not report any initiatives. Our findings suggest that urban adaptation is in the early stages, but there are still substantive examples of governments taking leadership regardless of wealth levels and institutional barriers.